176k views
3 votes
What is (f+g)(x)?

f(x)=x2−36

g(x)=x3+2x2−10



Enter your answer in the box.

2 Answers

3 votes

Answer:

x^3+3x^2-46

Explanation:

hope this helps

User Tine
by
6.0k points
4 votes

Answer:

( f + g )(x) is x³ + 3x² - 46

Explanation:

Given: f(x) = x² - 36 and g(x) = x³ + 2x² - 10

we have to find ( f + g )(x)

( f + g )(x) = f(x) + g(x) = ( x² - 36 ) + ( x³ + 2x² - 10 )

= x² - 36 + x³ + 2x² - 10

= x³ + (1+2)x² - 36 - 10

= x³ + 3x² - 46

Therefore, ( f + g )(x) is x³ + 3x² - 46

User KRB
by
6.3k points